-
Notifications
You must be signed in to change notification settings - Fork 0
/
Copy pathmain (10).f95
154 lines (153 loc) · 3.91 KB
/
main (10).f95
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
PROGRAM Q2
IMPLICIT NONE
real,dimension(20,20)::A,NA,B
real,dimension(20)::X,B1
integer n,i,j,k,l
real d,c,sum,temp,max,prod
A=0
B=0
NA=0
B1=0
X=0
do n=5,15,5
prod=1
do i=1,n
c=i
do j=1,n
d=j
A(i,j)=1.0/(c+d-1)
enddo
enddo
do i=1,n
sum=0
do j=1,n
sum=sum+A(i,j)
enddo
B1(i)=sum
enddo
do i=1,n
B(i,i)=1
enddo
do k=1,n-1
j = maxloc(abs(A(k:n,k)),dim=1)+k-1
if (j/=k) then
do l=k,n
temp=A(k,l)
A(k,l)=A(j,l)
A(j,l)=temp
enddo
do l=1,n
temp=B(k,l)
B(k,l)=B(j,l)
B(j,l)=temp
enddo
endif
do i=1,n-k
c=(A(k+i,k))/(A(k,k))
A(k+i,k+1:n) = A(k+i,k+1:n)-(c*(A(k,k+1:n)))
B(k+i,1:n) = B(k+i,1:n)-(c*(B(k,1:n)))
enddo
enddo
do j=1,n
do k=n,1,-1
sum=0
do i=k+1,n
sum=sum+(A(k,i)*(B(i,j)))
enddo
b(k,j)=((b(k,j))-sum)/(a(k,k))
enddo
enddo
do i=1,n
prod=prod*a(i,i)
enddo
print *," A(i,j) = 1 / (i+j-1)"
print *," n = ", n
print *," INVERSE MATRIX "
print *," Value of determinant ", prod
do i=1,n
print *, (b(i,j), j=1,n)
enddo
do i=1,n
sum=0
do j=1,n
sum=sum+(b(i,j))*(B1(j))
enddo
X(i)=sum
enddo
print *,"X"
print *,(X(i), i=1,n)
enddo
A=0
B=0
NA=0
B1=0
X=0
do n=5,15,5
prod =1
do i=1,n
c=i
do j=1,n
d=j
A(i,j)=(sqrt(2.0/(n+1)))*(sin(i*j*3.14159/(n+1)))
enddo
enddo
do i=1,n
sum=0
do j=1,n
sum=sum+A(i,j)
enddo
B1(i)=sum
enddo
do i=1,n
B(i,i)=1
enddo
do k=1,n-1
j = maxloc(abs(A(k:n,k)),dim=1)+k-1
if (j/=k) then
do l=k,n
temp=A(k,l)
A(k,l)=A(j,l)
A(j,l)=temp
enddo
do l=1,n
temp=B(k,l)
B(k,l)=B(j,l)
B(j,l)=temp
enddo
endif
do i=1,n-k
c=(A(k+i,k))/(A(k,k))
A(k+i,k+1:n) = A(k+i,k+1:n)-(c*(A(k,k+1:n)))
B(k+i,1:n) = B(k+i,1:n)-(c*(B(k,1:n)))
enddo
enddo
do j=1,n
do k=n,1,-1
sum=0
do i=k+1,n
sum=sum+(A(k,i)*(B(i,j)))
enddo
b(k,j)=((b(k,j))-sum)/(a(k,k))
enddo
enddo
print *," A(i,j) = (2/n+1)**(0.5) * sin(ij/n+1)"
do i=1,n
prod=prod*a(i,i)
enddo
print *," determinant = ",prod
print *," n =",n
print *," INVERSE MATRIX "
do i=1,n
print *, (b(i,j), j=1,n)
enddo
do i=1,n
sum=0
do j=1,n
sum=sum+(b(i,j))*(B1(j))
enddo
X(i)=sum
enddo
print *,"X"
print *,(X(i), i=1,n)
enddo
end program q2